Diatom counts from sediment core HZM19, Holzmaar (West-Eifel Volcanic Field, Germany) - María Luján García; Stella Birlo; Petra Zahajská; Giulia Wienhues; Martin Grosjean; Bernd Zolitschka (PANGAEA, 2024)
Diatom analyses were done following (Battarbee, 1986; Battarbee et al., 2002; doi:10.2478/s11756-019-00407-8). Including an updated list of names. The sediment core HZM19 was collected in 2019, from Holzmaar, West-Eifel Volcanic Field in Germany using a UWITEC Piston Corer. The sediment core was collected to reconstruct environmental and climate changes of Holzmaar for the last 16,000 years cal BP. Particularly in this data set we cover between 2450-2950 cal BP. An aliquot of each freeze-dried sample was processed with standard procedures (Battarbee, 1986; Battarbee et al., 2002). Only species with >=5% relative abundance in at least two samples were used for further analyses. Species acronyms are listed seperately.